Prediction of the lithium-ion cell performance via concentration profile simulation - Yusof, Norzihani; Hasan Basari, Abd Samad; Ibrahim, Nuzulha Khilwani (2012)
This paper presents the lithium-ion concentration profile simulation in the cathode for the half cell to predict the performance of the lithium-ion cell. By utilizing the mathematical model from the identified theoretical principles, the lithium-ion cell system in the solution phase is used to describe the discharge behavior of the rechargeable cell based on the simulated concentration profile. For this work, the cathode is the positive electrode employing LiMn2O4 as the active material. In addition, the numerical technique namely Finite Difference Method is used to solve the material balances equation of lithium-ion cell. This method is compared to other methods to identify the concentration profile. Nevertheless, the solutions in this paper merely focus on the concentration profile of lithium-ion in the cathode under galvanostatic discharge in the half cell.